The epigenetic uranium ore mineralization of the Gayvoron ore occurrence of the Ukrainian shield - Karly, Z.V.; Syomka, V. O.; Bondarenko, S.M.; Stepanyuk, L.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
For the first time for Precambrian rocks of the Ukrainian Shield in the crack zones of aplite-pegmatoid granitoids extending over 330-m depths, the epigenetic uranium ore mineralization is determined. The fact indicates that the supergene alteration processes occur not only on the crystalline basement surface, but at large depths of fault zones. Uranium was deposited as lowtemperature oxides and hydroxides in the cracks filled with hydromica-carbonate aggregates, iron oxides, and manganese oxides. Coronadite, a rare mineral which have not been found before in Precambrian rocks of the Ukrainian Shield, is detected as well. A mineral formed due to the decay of pitchblende and uranium oxide-hydroxide minerals, skupite, is first detected. Skupite is a characteristic indicative mineral for prospecting the infiltration-type uranium deposits.